Bibliometric and visualization analysis of stem cell therapy for meniscal regeneration from 2012 to 2022 - Yang, Zhen; Fan, Zejun; Wang, Du; Li, Hui; He, Zihao; Xing, Dan; Lin, Jianhao (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Meniscus injuries, a common joint disease caused by long-term wear, trauma and inflammation, usually cause chronic dysfunction and pain in the joint. Current clinical surgeries mainly aim to remove the diseased tissue to alleviate patient suffering instead of helping with meniscus regeneration. As an emerging treatment, stem cell therapy has been verified to facilitate meniscus regeneration effectively. The purpose of this study is to investigate the publication conditions of stem cell therapy for meniscal regeneration and to visualize the research trends and frontiers. Methods: Relevant publications relevant to stem cells for meniscal regeneration was retrieved SCI-Expanded of the Web of Science database from 2012 to 2022. Research trends in the field were analysed and visualized by CiteSpace and VOSviewer. Results: A total of 354 publications were collected and analysed. The USA contributed the largest number of publications (118, 34.104%). Tokyo Medical Dental University has contributed the largest number of publications (34) among all full-time institutions. Stem cell research therapy has published the largest number of researches on stem cells for meniscal regeneration (17). SEKIYA. I contributed the majority of publications in this field (31), while Horie, M was the most frequently cited authors (166). #1 tissue engineering, #2 articular cartilage, #3 anterior cruciate ligament, #4 regenerative medicine, #5 scaffold are the chief keywords. This indicates that the current research hotspot has been transformed from basic surgical research to tissue engineering. Conclusion: This is the first visualized and bibliometric study to thoroughly construct the development trends and knowledge structure in the research field of stem cell therapy for meniscal regeneration in the past 10 years. The results thoroughly summarize and visualize the research frontiers, which will shed light on the research direction of stem cell therapy for meniscal regeneration.